Scholastic achievement and intelligence: behavioral genetic analysis in a sample of Croatian twins - Butković, Ana (Array, 2007)
Previous studies have shown that both scholastic achievement, as measured by either school grades or standardized achievement test scores, and intelligence are influenced by genetic and environmental factors, while their correlation has been due primarily to overlapping genetic influences (S.A. Petrill and B.Wilkerson, 2000, Educ. Psychol. Rev., 12, 185-199). However, the majority of studies have examined that relationship in children typically aged between 5 and 13 years, with only one study using a sample aged on average 17 years. In our study, the relationship between scholastic achievement and intelligence was examined in a sample of twins (71 MZ, 78 DZ pairs) aged on average 17 years. Four different measures of intelligence were used, two that measured spatial abilities (visualization and spatial orientation) and two that measured verbal abilities (word fluency and vocabulary). Scholastic achievement was measured by three school grades obtained at the end of the first semester, Croatian, Mathematics and an average grade from all subjects. Univariate analyses indicated that the best fitting model for all measures includes additive genetic (A) and non-shared environmental (E) influences, with heritability estimates in the .60 to .80 range. Bivariate analyses between each of four intelligence measures as well as between composite intelligence score obtained as a factor score from four measures, and each of scholastic achievement measures were done using AE correlated factors model. Results showed that two verbal abilities and composite intelligence score shared from 49%-67% of genetic influences with each of scholastic achievement measures. For spatial abilities, shared genetic influences were found between spatial orientation and Mathematics grade (36%), and between visualization and Croatian (40%) and average grade (24%). Visualization also shared environmental influences with Mathematics (33%) and average grade (37%).